PENDIDIKAN KARAKTER BERBASIS PESANTREN DI SEKOLAH MENENGAH KEJURUAN ASY-SYAFI’IYYAH KEBONAGUNG PAKISAJI MALANG - Moch Syihabul Millah; Ika Ratih Sulistiani; Imam Safi’i (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
The Indonesian people today have been faced with various problems that are alternating and in various forms and have not been resolved properly. One of the problems is the decline in national character education which is motivated by the rapid development of technology, and the interaction of students in daily life. Thus, if parents do not educate and provide a strong religious foundation, it is feared that it will cause a decline in the character of students. SMK Asy-Syafi'iyyah Kebonagung is a formal educational institution located under the auspices of the PPIQ Asy-Syafi'iyyah. Pesantren is one forum that is quite relevant in the process of inculcating and improving character education in students, the Asy-Syafi'iyyah Vocational School applies pesantren-based character education in shaping its student character. Islamic boarding school-based character education at Asy-Syafi'iyyah Vocational School is maximized by various series of pesantren activities such as madrasa diniyyah, Khitobah, routine activities of public recitation and istoriah thoriqoh every month, as well as exemplary caregivers in talking to anyone, humble, and living simple, so that they can form the personality of students who are independent, responsible for acting, able to control emotions, religious, and Islamic music extracurricular.